The urban question in the context of the “double world” - Kyvelou, Stella (Homo Virtualis, 2019)
Once the principle of the inseparability of the material world and cyber territory has been admitted, the question put to the urban planner is being transformed. The transition from the representation of two separate worlds - the physical on the one hand and the digital on the other - to a representation of a “double world” in the sense of the indivisible inter-connection of the physical and the digital, leads to a change of paradigm in abstraction and representation. By accepting the principle of considering the material world and the cyber territory (and not cyberspace) as an indivisible whole, we come up to realize that the urban question changes. If, in the past, our thoughts and studies were aimed at seeking a common world that we should discover and maintain, the modern world is not presumed to belong exclusively in the material reality. The planner’s work, therefore, should certainly take into account this interconnection, the discontinuous, fragmentary involvement, of matter and information. However, this phenomenon is not new since the symbolic dimension of cities, architecture and space in general has always closely interwoven representation and the real world. The difference is that there was then a connection with a particular territory or a national identity. Today, this ancient territorial reference is weakening, although there are signs of reversion to it. Based on these observations, the paper will discuss the evolution of the urban question under the assumption of the indivisible “double world” and the augmented territories.